Transmission of agricultural ethnobiological knowledge to the younger generation through the Ngarot and Durugan traditions in Lelea Village Indramayu - Fitriyani, Fitriyani; Wicaksono, Harto (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2026)
The regeneration of young farmers remains a critical issue for the sustainability of food security, yet mechanisms for the intergenerational transmission of agricultural knowledge within local cultural contexts have not consistently functioned. This study explores the Ngarot and Durugan traditions in Lelea Village, Indramayu Regency, as arenas for transmitting ethnobiological agricultural knowledge to younger generations. Employing a qualitative case study design with an interpretive ethnographic approach, data were collected through field observations, in-depth interviews with purposively selected traditional leaders, farmers, and young people, as well as primary and secondary documentation. Based on Cavalli-Sforza and Feldman’s theory of cultural transmission, the findings indicate that the Ngarot and Durugan traditions function as mechanisms of agricultural enculturation that are selective, symbolic, and pedagogically unstructured. The study underscores that the sustainability of agricultural knowledge is not automatically ensured through cultural rituals, but depends on the depth of practical engagement, the duration of learning processes, and the involvement of cross-generational actors. The findings suggest that participatory ethnopedagogical approaches may offer a critical framework to support the regeneration of young farmers and local food security.   Regenerasi petani muda menjadi isu krusial dalam keberlanjutan ketahanan pangan. Namun, mekanisme pewarisan pengetahuan pertanian dalam konteks budaya lokal belum selalu berjalan secara konsisten.  Penelitian ini mengkaji tradisi Ngarot dan Durugan di Desa Lelea, Kabupaten Indramayu, sebagai arena pewarisan pengetahuan etnobiologi pertanian kepada generasi muda. Penelitian ini menggunakan desain studi kasus kualitatif dan pendekatan etnografis interpretatif, data dikumpulkan melalui observasi lapangan, wawancara mendalam secara purposif dengan tokoh adat, petani dan generasi muda, serta dokumentasi primer dan sekunder. Berdasarkan teori transmisi budaya Cavalli-Sforza dan Feldman, temuan menunjukkan bahwa tradisi Ngarot dan Durugan berfungsi sebagai mekanisme enkulturasi pertanian yang bersifat selektif, simbolik dan tidak terstruktur secara pedagogis. Studi ini menegaskan bahwa keberlanjutan pengetahuan pertanian tidak secara otomatis dijamin melalui ritual budaya, melainkan bergantung pada kedalaman praktik, durasi pembelajaran, dan keterlibatan aktor lintas generasi. Temuan ini menyarankan bahwa pendekatan etnopedagogi partisipatif dapat menawarkan kerangka kerja kritis untuk mendukung regenerasi petani muda dan ketahanan pangan lokal.